Distributed Database Using Mobile Agent - Sugiantoro, Bambang; Wardoyo, Retantyo; Hartati, Sri; Istiyanto, Jazi Eko (IJID (International Journal on Informatics for Development), 2012)
The number of sources of information brings several problems, among them about how to combine the distributed data storage and different. Information on an organization or company is usually stored in separate locations and different formats. When there is an increase in storage capacity and the amount of information search costs, the company faced with an abundance amount of data. System development methodology used is object oriented design with a development framework